What Explains the Speed of Recovery from Banking Crises? - Christian Ambrosius (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
While much research has been done on causes and effects of banking crises, little is known about what determines recovery from banking crises, despite of large variations in post-crises performances across countries. In order to identify local and global factors that determine the length of recovery (i.e. the time it takes until countries reach their pre-crisis level of per capita GDP), this paper employs event history analysis on 138 incidents of banking crises between 1970 and 2013. Cox proportional hazards show that crises characteristics, specific country conditions as well as external factors affect the duration of recovery. Regarding domestic factors, simultaneous currency crises, large financial sectors and overvalued currencies are associated with later recovery. Regarding external factors, a low growth of world trade has a negative effect on recovery, and so does uncertainty in financial markets as reflected in high gold prices. Moreover, contractionary monetary policy of the US Fed as Central Bank of the international key currency has a negative effect on the length of recovery in middle-income countries. In general, the dominance of global variables as well as variables related to the exchange-rate underline that the speed of recovery is particularly constrained by countries' positions within the global economy.
Keywords: H12; E44; O23; 330